2015
DOI: 10.1093/aobpla/plv102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic consequences of cladogenetic vs. anagenetic speciation in endemic plants of oceanic islands

Abstract: This paper presents for the first time a comparison of the genetic consequences of two different types of speciation in plants of an oceanic island. Genetic data, using two different DNA methods, were obtained from more than 4,000 plants from the two major islands of the Juan Fernández Archipelago (Chile). Results show that some immigrant populations undergo major splitting events and harbor limited genetic diversity within each evolving line. In contrast, other immigrant populations establish and enlarge, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…Microsatellites -Twelve microsatellite markers were initially isolated from species of Erigeron based on repeatability and scoring convenience (Takayama et al 2012a). Four combinations of multiplex PCR amplification were performed using the 5′-tailed primer method (Boutin-Ganache et al 2001) and a slightly modified protocol of the Qiagen multiplex PCR kit (Qiagen, Hilden, Germany) following Takayama et al (2012a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsatellites -Twelve microsatellite markers were initially isolated from species of Erigeron based on repeatability and scoring convenience (Takayama et al 2012a). Four combinations of multiplex PCR amplification were performed using the 5′-tailed primer method (Boutin-Ganache et al 2001) and a slightly modified protocol of the Qiagen multiplex PCR kit (Qiagen, Hilden, Germany) following Takayama et al (2012a).…”
Section: Methodsmentioning
confidence: 99%
“…Four combinations of multiplex PCR amplification were performed using the 5′-tailed primer method (Boutin-Ganache et al 2001) and a slightly modified protocol of the Qiagen multiplex PCR kit (Qiagen, Hilden, Germany) following Takayama et al (2012a). The combinations with four different dyes were as follows: ER-G241H, ER-G7RC3, ER-CO124 with 6-FAM; ER-G3OOM, ER-HAJZC, ER-HDLDG with VIC; ER-HE8SM, RER-HANK8, ER-GZHZ0 with NED; ER-HKNVD, ER-HCHKA, ER-GUJTP with PET.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1987; Stuessy and Ono 1998; Emerson 2002; Whittaker and Fernandez-Palacios 2007, Bramwell and Caujapé-Castells 2011; Silva et al . 2015; Takayama et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors pertaining to the evolutionary history of the species, including speciation mechanisms (anagenesis vs. cladogenesis) and other events such as past hybridization and polyploidization, should also be considered for interpreting genetic diversity patterns (Soltis and Soltis, 2000;Stuessy et al, 2006;Stuessy et al, 2014). It has been proposed, for example, that the Galapagos endemic shrub Galvezia leucantha harbors high levels of genetic diversity in part due to populations from different islands maintaining some gene flow (Guzmán et al, 2016); thus, all these populations still conform a single species (as observed in anagenesis) (Stuessy et al, 2014;Takayama et al, 2015). Furthermore, the reproductive biology (outcrossing vs. selfing vs. clonal reproduction) and dispersal mechanisms of the species are also relevant factors that explain genetic diversity and structure (Crawford and Whitney, 2010).…”
Section: Introductionmentioning
confidence: 99%